2023
DOI: 10.1186/s12879-023-08029-x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and acceptability of COVID-19 vaccine among residents in rural communities in Ghana: a multi-regional study

Abstract: Background The Coronavirus Infectious Disease 2019 (COVID-19) pandemic has continuously affected human life with several devastating effects. Currently, there are effective vaccines to protect people from COVID‐19 and the World Health Organization (WHO) has highlighted strategies to influence COVID-19 vaccine uptake in hard-to-reach communities in Ghana. However, prior studies on COVID-19 vaccine acceptability in Ghana are online surveys targeting the literates and those in urban areas, leaving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…Similar to what was observed in this study, a study by Mohamed et al in Malaysia also reported higher acceptance of Covid-19 vaccine among people with higher knowledge of the pandemic [ 29 ]. However, a multi-regional study among the general public in Ghana reported a contradictory result [ 30 ]. Their study did not find any significant association between vaccine acceptance and knowledge of Covid-19.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to what was observed in this study, a study by Mohamed et al in Malaysia also reported higher acceptance of Covid-19 vaccine among people with higher knowledge of the pandemic [ 29 ]. However, a multi-regional study among the general public in Ghana reported a contradictory result [ 30 ]. Their study did not find any significant association between vaccine acceptance and knowledge of Covid-19.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical analysis was conducted using SPSS 23.0 (SPSS, Inc., Chicago, IL, USA), R software (version 4.2.1), and GraphPad Prism 8.0 software (GraphPad, Inc., La Jolla, CA, USA) [ 57 , 58 ]. Each experiment was repeated 3 times on 3 samples to ensure robustness and reproducibility.…”
Section: Methodsmentioning
confidence: 99%
“…It is crucial to recognize that demographic factors such as employment status, rural or urban residency, occupation, level of experience, and political party affiliation among opposition voters were not extensively examined in the assessment of factors influencing COVID-19 vaccine acceptance and hesitancy in Ghana (see Figure 4). [5], [8], [11], [13], [27], [34], [37], [49], [44] 9 Gender [6], [8], [11], [30], [35], [37], [42], [44] 8 Religion [8], [13], [15], [27], [34] [42], [44], [49] 8 Age [9], [11], [15], [27], [42], [49] 6 Marital Status [12], [37], [42] 3 Primary source of information about COVID-19 vaccine [11], [13], [44] 3 According to Backhaus [50], urban residency and current pregnancy were significantly and positively associated with refusing vaccination against COVID-19, whereas age, savings, and using contemporary contraceptives were significantly and negatively associated with refusing vaccination. Additional research by Hwang et al [51] indicates that younger age, lack of religious affiliation, political conservatism, and lower family income are also substantially associated with vaccine hesitancy.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…A study conducted by Amponsah-Tabi et al [5] during the period of the COVID-19 vaccine rollout examined the influence of media awareness on the acceptance of vaccination. This study highlighted that those who had prior knowledge or education about vaccination were influenced by the inclusion of media awareness, hence influencing the dynamics of COVID-19 vaccine acceptability.…”
Section: Introductionmentioning
confidence: 99%